The Helper - Community Health Workers Support Unit, AMREF (African Medical and Research Foundation (AMREF), 1980)
This newsletter is about people who help their neighbours to help themselves. What is the name for these people? Well, every place seems to have a different name. Some of the names used in Kenya are Public Health Aide, Clan Health Worker, Community Health Worker, and Village Health Helper. ln three places the name used is the local word for helper: Atethesia in Kibwezi, Jakony in Saradidi and Athesia in Maua. Do you think there mighl be one name which would be good for all such worked everywhere in Kenya? Such a name would help us to be United. lt would also, make the whole country know about our work. What are your ideas about a single name for people who work to improve health in their own community or village?
A newsletter between people working with village health programmes
Keywords: Nangina; Clan Health Workers (CHWS); Roy Shaffer; Saradidi programme